Dual reactive coating composition, preparation thereof and use thereof
By using a dual reactive coating composition, the problems of post-curing, cracking and phase separation in the reactive silane-based system in automotive coatings in the prior art are solved, and the durability, chemical resistance and appearance properties of the coating are achieved. promote.
Patent Information
- Application Number
- CN202180033161.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-07
- Filing Date
- 2021-05-03
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-05-03
AI Technical Summary
The existing reactive silane-based systems have problems of post-curing, cracking and phase separation in automotive coatings, resulting in degradation of durability, chemical resistance and appearance performance.
Dual reactive coating compositions are employed, comprising 24% to 90% by weight of crosslinkable silane functional monomers and/or oligomers and/or polymers, 9% to 75% by weight of unsaturated monomers and/or or oligomers and/or polymers, 0.5% to 10% by weight of initiator and 0.5% to 10% by weight of catalyst.
The resulting coating exhibits good durability, chemical resistance and appearance properties, avoiding problems of post-curing, cracking and phase separation.
Smart Images

Figure BDA0003926438840000241 
Figure BDA0003926438840000242 
Figure BDA0003926438840000261
Abstract
Description
Technical Field
[0001] The present invention relates to a dual reactive coating composition, and more particularly to a dual reactive coating composition used as automobile topcoat, and the preparation and use thereof.
[0002] background
[0003] Nanocomposites are materials consisting of finely dispersed inorganic nanoparticles in a continuous polymer matrix. Inorganic nanoparticles are in most cases produced by the sol-gel process from respective precursors which hydrolyze and condense to form particles of different morphologies. Transparent organic-inorganic composite films can be prepared by dispersing preformed particles in polymers using common polymer processing such as extrusion or by dispersing them in monomers and then polymerizing to form a continuous polymer phase. However, in both cases, the structure of the organic and inorganic phases, the phase morphology and the presence of covalent bonds between the two phases significantly influence the properties of these composites.
[0004] For automotive coatings that require a high degree of visual appearance as well as long-term durability, reactive polymer systems with silane functionality are potentially attractive to provide new properties to conventional coatings based on organic-inorganic composites, such as enhanced scratch and chemical resistance, while allowing different curing methods while meeting environmental requirements.
[0005] Hybrid silane-containing polymers have been widely used to date in wet-reactive sealants and adhesives as well as in building materials. These reactive resins have hydrolyzable alkoxysilanes as end groups or on side chains, which react via a hydrolysis mechanism to form a silsesquioxane network. The finely dispersed inorganic domains provide the polymer matrix with excellent properties such as good chemical resistance, improved scratch resistance, good weathering resistance and refined surface adhesion. However, some common disadvantages of reactive silane-based systems are the occurrence of post-curing, cracking and phase separation, which leads to a decrease in properties such as durability, chemical resistance, appearance, etc., and thus greatly limits their use in automotive coatings. SUMMARY OF THE INVENTION
[0007] In one aspect, the present invention provides a dual reactive coating composition comprising
[0008] a). 24 to 90% by weight of crosslinkable silane-functional monomers and / or oligomers and / or polymers;
[0009] b). 9 to 75% by weight of one unsaturated monomer and / or oligomer and / or polymer;
[0010] c) 0.5 wt % to 10 wt % of an initiator; and
[0011] d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition.
[0012] In another aspect, the present invention provides a dual reactive coating composition comprising
[0013] a). 24 to 90% by weight of crosslinkable silane-functional monomers and / or oligomers and / or polymers;
[0014] b). 9 to 75% by weight of unsaturated polyester and / or polyurethane modified oligomers and / or polyester modified oligomers;
[0015] c) 0.5 wt % to 10 wt % of an initiator; and
[0016] d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition.
[0017] In another aspect, the present invention provides a dual reactive coating composition comprising
[0018] a). 24 to 90% by weight of a crosslinkable silane-functional polymer;
[0019] b). 9 to 75% by weight of unsaturated polyester;
[0020] c) 0.5 wt % to 10 wt % of an initiator; and
[0021] d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition.
[0022] In another aspect, the present invention provides a film obtained by curing and drying the dual reactive coating composition of the present invention.
[0023] In another aspect, the present invention provides a substrate coated with the dual reactive coating composition of the present invention.
[0024] In another aspect, the present invention provides a method for preparing the dual reactive coating composition of the present invention by mixing the following components:
[0025] a). 24 to 90% by weight of crosslinkable silane-functional monomers and / or oligomers and / or polymers;
[0026] b). 9 to 75% by weight of one unsaturated monomer and / or oligomer and / or polymer;
[0027] c) 0.5 wt % to 10 wt % of an initiator; and
[0028] d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition.
[0029] In another aspect, the present invention provides a method for preparing the dual reactive coating composition of the present invention by mixing the following components:
[0030] a). 24 to 90% by weight of crosslinkable silane-functional monomers and / or oligomers and / or polymers;
[0031] b). 9 to 75% by weight of unsaturated polyesters and / or polyester-modified oligomers;
[0032] c) 0.5 wt % to 10 wt % of an initiator; and
[0033] d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition.
[0034] In another aspect, the present invention provides a method for preparing the dual reactive coating composition of the present invention by mixing the following components:
[0035] a). 24 to 90% by weight of a crosslinkable silane-functional polymer;
[0036] b). 9 to 75% by weight of unsaturated polyester;
[0037] c) 0.5 wt % to 10 wt % of an initiator; and
[0038] d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition.
[0039] In another aspect, the present invention provides a roll-to-roll coating composition, which comprises the dual reactive coating composition of the present invention, a reactive diluent and an additive, wherein the solid content of the obtained roll-to-roll coating composition is not less than 90 wt %, preferably not less than 95 wt %.
[0040] In a further aspect, the present invention provides a 1K clearcoat composition comprising the dual reactive coating composition of the present invention, a reactive diluent, an additive and a cosolvent, wherein the VOC (volatile organic compound) of the obtained clearcoat composition is not more than 420 g / L, preferably not more than 350 g / L.
[0041] It was unexpectedly discovered that by using a dual reactive system, the resulting coating exhibits good properties of durability, chemical resistance, appearance, etc. DETAILED DESCRIPTION OF THE INVENTION
[0043] As used in this specification and the appended claims, the following terms have the following definitions:
[0044] The words "a", "an", "the", when used to specify a term, include both the plural and singular forms of the term.
[0045] Unless otherwise indicated, all percentages are mentioned by weight.
[0046] The term "and / or" includes the meanings "and", "or" and all other possible combinations of the elements connected with this term.
[0047] As used herein, the term "oligomer" refers to a homopolymer having 2 to 3 repeating units of a single monomeric compound.
[0048] As used herein, the term "1K" refers to a composition comprising one component, which may be a mixture of several compounds.
[0049] The term "2K" or "two-component" as used herein refers to a composition comprising two components, each of which may also be a mixture of several compounds. If desired, the two components may be blended together. The two components may also be two separate buckets that can be mixed at the application site.
[0050] As used herein, the term "solids content" refers to the weight percent of non-volatile materials contained in a suspension, such as a paint, lacquer, or the like.
[0051] The term "dual reactivity" as used herein refers to two reactions in the coating composition, namely (1) polymerization of olefinic double bonds contained in the monomers and / or oligomers and / or polymers, and (2) reaction of hydrolyzable alkoxysilane or organoalkoxysilane groups in the monomers and / or oligomers and / or polymers.
[0052] As used herein, the term "crosslinkable silane-functional polymer" refers to polymers and copolymers containing crosslinkable silane functionality derived from the (co)polymerization of silane-functional monomers, such as vinyl silanes.
[0053] As used herein, the term "crosslinkable silane functional oligomer" refers to oligomers and cooligomers containing crosslinkable silane functionality derived from the (co)oligomerization of silane functional monomers, such as vinyl silanes.
[0054] As used herein, the term "reactive diluent" refers to a substance that reduces the viscosity of the coating to facilitate processing and subsequently becomes part of the coating by (co)polymerization with any other components of the coating.
[0055] As used herein, the term "co-solvent" refers to a substance added in small amounts to a primary solvent or reactive diluent to increase the solubility of a poorly soluble compound.
[0056] Silane functional monomers and / or oligomers and / or polymers
[0057] The silane functional monomer is preferably a vinyl alkoxysilane monomer in the present invention. The vinyl group will participate in free radical polymerization, while the alkoxy group will undergo hydrolysis and (self) condensation reactions in the coating composition. Preferably, the vinyl alkoxysilane monomer is at least one selected from vinyl trimethoxysilane, vinyl methyl dimethoxy silane, vinyl triethoxy silane, vinyl tri (2-methoxyethoxy) silane, vinyl tri (isopropoxy) silane and 3-methacryloxypropyl trimethoxy silane.
[0058] The silane functional oligomer and / or polymer is an acrylosilane oligomer and / or polymer, which is a polymerization product of 20 wt % to 50 wt % of an ethylenically unsaturated vinyl alkoxy silane monomer represented by the general formula I, 50 wt % to 80 wt % of an ethylenically unsaturated acrylate monomer, and 0 to 30 wt % of an ethylenically unsaturated monomer selected from one or both of styrene and methacrylate monomers, based on the total weight of the acrylosilane polymer.
[0059] H2C=CH-(CH2) n -Si-(R1) m (R2) 3-m
[0060] wherein R1 is an aryl group or an alkyl group having C1-C6, R2 is an alkoxy group having C1-C6, m is 0 or 1, and n is an integer from 0 to 3.
[0061] The ethylenically unsaturated acrylate monomer is preferably an alkyl acrylate having a C1-C12 alkyl group, more preferably at least one selected from methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, pentyl acrylate, ethylhexyl acrylate, nonyl acrylate and lauryl acrylate. Alicyclic acrylates such as isobornyl acrylate, trimethylcyclohexyl acrylate and tert-butylcyclohexyl acrylate can be used. Acrylic acid aryl esters such as benzyl acrylate can be used. Polyacrylate monomers such as 1,3-butylene glycol diacrylate and cyclohexanedimethanol diacrylate can be used, and neopolyacrylate monomers such as 1,3-butylene glycol diacrylate, 1,4-butylene glycol diacrylate, 1,6-hexanediol diacrylate, cyclohexanedimethanol diacrylate, neopentyl glycol diacrylate, pentaerythritol triacrylate, trimethylolpropane triacrylate, diamino ester diacrylate, and amino ester triacrylate can be used. Other acrylate monomers may also be used, such as silane functional acrylates. Mixtures of the above monomers may also be used.
[0062] The methacrylate monomer is preferably an alkyl methacrylate monomer, more preferably at least one selected from methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, isobutyl methacrylate, amyl methacrylate, hexyl methacrylate, ethylhexyl methacrylate, octyl methacrylate, nonyl methacrylate and lauryl methacrylate. Alicyclic methacrylates such as trimethylcyclohexyl methacrylate and tert-butylcyclohexyl methacrylate can be used. Methacrylate aryl esters such as benzyl methacrylate can be used. The styrene monomer is preferably a vinyl aromatic compound such as styrene and methyl styrene.
[0063] The acrylsilane polymer may contain hydroxyl functional groups provided by hydroxyalkyl acrylates and methacrylates having C1-C4 alkyl groups, such as hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and hydroxybutyl methacrylate.
[0064] Preferably, the crosslinkable silane functional oligomer or polymer has a weight average molecular weight below 30,000, preferably below 20,000, and the crosslinkable silane functional polymer has a hydroxyl value of 0 to 150 mg KOH / g and an acid value of 0 to 50 mg KOH / g.
[0065] The solvent used to form the acryl silane polymer is a petroleum distillate. Alcohols such as methanol, ethanol, n-propanol, isopropanol, butanol, sec-butanol, isobutanol and propanol can be used. Ketones such as acetone, butanone, amyl ketone, hexanone and methyl ethyl ketone can be used. Alkyl esters of acetic acid, propionic acid and butyric acid can be used, such as ethyl acetate, butyl acetate and amyl acetate. Ethers such as tetrahydrofuran, diethyl ether and ethylene glycol and polyethylene glycol monoalkyl and dialkyl ethers such as cellosolve and carbitol and glycols such as ethylene glycol and propylene glycol can also be used. The above monomers can be used in combination.
[0066] Peroxy or azo polymerization initiators can be used to prepare acrylsilane polymers, such as benzoyl peroxide, di-tert-butyl peroxide, lauroyl peroxide, tert-butyl peroxypivalate, tert-butyl peroxy-2-ethylhexanoate, 2,2'-azobisisobutyronitrile, 2,2'-azobis-2,4-dimethylvaleronitrile, 2,2'-azobis-methylbutyronitrile, and 1,1'-azobis-cyanocyclohexane.
[0067] The present invention unexpectedly discovered a synthesis procedure based on an optimized feeding strategy, wherein the composition of the monomer feed is changed in multiple steps during the reaction process. These optimized feeding strategies lead to uniform incorporation of vinyl alkoxysilanes while resulting in a significant reduction in monomer residues after polymerization. Homogeneous silane-functional polymers are obtained, which have excellent film-forming and cross-linking properties and provide excellent flexibility. Therefore, crack formation is substantially suppressed without the addition of any film-forming polymers or additives, such as curing agents and plasticizers.
[0068] Preferably, the crosslinkable silane-functional polymer is prepared by a method comprising two steps: in a first step, vinyl alkoxysilane monomer, (meth)acrylate monomer and optional styrene monomer and initiator are mixed with an organic solvent and heated, and in a second step, (meth)acrylate monomer and optional styrene monomer and initiator are added, wherein in the second step, the (meth)acrylate monomer and optional styrene monomer are added in no less than two batches, and the time between each batch is no less than half an hour and the weight ratio between the (meth)acrylate monomer and the optional styrene monomer added in each batch is 1:15 to 15:1.
[0069] More preferably, the crosslinkable silane-functional polymer is prepared by a method comprising two steps: in a first step, vinyl alkoxysilane monomer, (meth)acrylate monomer and optional styrene monomer and initiator are mixed with an organic solvent and heated, and in a second step, (meth)acrylate monomer and optional styrene monomer and initiator are added, wherein in the second step, the (meth)acrylate monomer and optional styrene monomer are added in not less than four batches, and the time between each batch is not less than 1 hour and the weight ratio between the (meth)acrylate monomer and optional styrene monomer added in each batch is 1:15 to 15:1.
[0070] As an example, a crosslinkable silane-functional polymer is prepared as follows:
[0071] The reactor is loaded with 100-500 parts by weight of Shellsol A and this initial charge is heated to 90-160° C. The reactor is placed under pressure (1.5-6.5 bar). Thereafter, over a period of 4-7 hours, an initiator solution (50-100 parts by weight of di-tert-butyl peroxide in 50-100 parts by weight of Shellsol A) is metered in at a uniform rate under stirring. Starting 0-30 minutes after the start of the initiator feed, feed 1 consisting of ethylenically unsaturated vinylalkoxysilane monomers is metered in at a uniform rate over a period of 0.5-2 hours under stirring. Starting 0-30 minutes after the start of the initiator feed, 500-1500 parts by weight of feeds 2 to 6 consisting of methyl methacrylate and n-butyl acrylate in a weight ratio of 0.1 to 10 are metered in at a uniform rate over a period of 0.5-2 hours for each feed under stirring. After complete addition of the initiator solution (0-60 minutes after the end of the addition of the monomer mixture), the reactor is heated to 100-180° C. and stirring is continued at the specified pressure for 5-90 minutes, and then a solution consisting of 5-50 parts by weight of di-tert-butyl peroxide in 5-50 parts by weight of Shellsol A is added again at a uniform rate over the course of 0.5-2 hours. Subsequently, the batch is maintained at the specified temperature and the specified pressure for a further 0.5-2 hours. Thereafter, the reaction mixture is cooled to 25-80° C. and depressurized to atmospheric pressure.
[0072] As another example, a crosslinkable silane-functional polymer is prepared as follows:
[0073] The reactor is loaded with 100-500 parts by weight of Shellsol A and this initial charge is heated to 90-160° C. The reactor is placed under pressure (1.5-6.5 bar). Thereafter, over a period of 4-7 hours, an initiator solution (50-100 parts by weight of di-tert-butyl peroxide in 50-100 parts by weight of Shellsol A) is metered in at a uniform rate under stirring. Starting 0-30 minutes after the start of the initiator feed, feed 1 consisting of ethylenically unsaturated vinylalkoxysilane monomers is metered in at a uniform rate over a period of 0.5-2 hours under stirring. Starting 0-30 minutes after the start of the initiator feed, 500-1500 parts by weight of feeds 2 to 6 consisting of styrene, methyl methacrylate and n-butyl acrylate in a weight ratio of 0.1 to 10 are metered in at a uniform rate over a period of 0.5-2 hours for each feed under stirring. After complete addition of the initiator solution (0-60 minutes after the end of the addition of the monomer mixture), the reactor is heated to 100-180° C. and stirring is continued at the specified pressure for 5-90 minutes, and then a solution consisting of 5-50 parts by weight of di-tert-butyl peroxide in 5-50 parts by weight of Shellsol A is added again at a uniform rate over the course of 0.5-2 hours. Subsequently, the batch is maintained at the specified temperature and the specified pressure for a further 0.5-2 hours. Thereafter, the reaction mixture is cooled to 25-80° C. and depressurized to atmospheric pressure.
[0074] As another example, a crosslinkable silane-functional polymer is prepared as follows:
[0075] 100-500 parts by weight of Shellsol A are loaded in the reactor and this initial charge is heated to 90-160° C. The reactor is placed under pressure (1.5-6.5 bar). Thereafter, over a period of 4-7 hours, an initiator solution (50-100 parts by weight of di-tert-butyl peroxide in 50-100 parts by weight of Shellsol A) is metered in at a uniform rate under stirring. Starting 0-30 minutes after the start of the initiator feed, feed 1 consisting of ethylenically unsaturated vinylalkoxysilane monomers is metered in at a uniform rate over a period of 0.5-2 hours under stirring. Starting 0-30 minutes after the start of the initiator feed, 500-1500 parts by weight of feeds 2 to 6 consisting of styrene, methyl methacrylate and ethylhexyl acrylate in a weight ratio of 0.1 to 10 are metered in at a uniform rate over a period of 0.5-2 hours for each feed under stirring. After complete addition of the initiator solution (0-60 minutes after the end of the addition of the monomer mixture), the reactor is heated to 100-180° C. and stirring is continued at the specified pressure for 5-90 minutes, and then a solution consisting of 5-50 parts by weight of di-tert-butyl peroxide in 5-50 parts by weight of Shellsol A is added again at a uniform rate over the course of 0.5-2 hours. Subsequently, the batch is maintained at the specified temperature and the specified pressure for a further 0.5-2 hours. Thereafter, the reaction mixture is cooled to 25-80° C. and depressurized to atmospheric pressure.
[0076] As another example, a crosslinkable silane-functional polymer is prepared as follows:
[0077] The reactor is charged with 100-500 parts by weight of butyl acetate and this initial charge is heated to 90-160° C. The reactor is placed under pressure (1.5-6.5 bar). Thereafter, over a period of 4-7 hours, an initiator solution (50-100 parts by weight of di-tert-butyl peroxide in 50-100 parts by weight of butyl acetate) is metered in at a uniform rate under stirring. 0-30 minutes after the start of the initiator feed, 300-700 parts by weight of ethylenically unsaturated vinylalkoxysilane monomers are metered in at a uniform rate under stirring over a period of 0.5-2 hours. In a first step, a monomer mixture consisting of 50-150 parts by weight of methyl methacrylate and 50-150 parts by weight of n-butyl acrylate is metered in simultaneously over a period of 0.5-2 hours under stirring at a uniform rate. In the second step, a monomer mixture consisting of 100-200 parts by weight of methyl methacrylate and 100-200 parts by weight of n-butyl acrylate is metered in at a uniform rate over a period of 0.5-2 hours with stirring. In the third step, a monomer mixture consisting of 50-150 parts by weight of methyl methacrylate and 50-150 parts by weight of n-butyl acrylate is metered in at a uniform rate over a period of 0.5-2 hours with stirring. In the fourth step, a monomer mixture consisting of 50-100 parts by weight of methyl methacrylate and 50-100 parts by weight of n-butyl acrylate is metered in at a uniform rate over a period of 0.5-2 hours with stirring. In the fifth step, a monomer mixture consisting of 25-75 parts by weight of methyl methacrylate and 25-75 parts by weight of n-butyl acrylate is metered in at a uniform rate over a period of 0.5-2 hours with stirring. After complete addition of the initiator solution (0-60 minutes after the end of the addition of the monomer mixture), the reactor is heated to 100-180° C. and stirring is continued at the specified pressure for 5-90 minutes, and then a solution consisting of 5-50 parts by weight of di-tert-butyl peroxide in 5-50 parts by weight of butyl acetate is added again over the course of 0.5-2 hours at a uniform rate. Subsequently, the batch is maintained at the specified temperature and the specified pressure for a further 0.5-2 hours. Thereafter, the reaction mixture is cooled to 25-80° C. and decompressed to atmospheric pressure.
[0078] As another example, a crosslinkable silane-functional polymer is prepared as follows:
[0079] The reactor is charged with 100-500 parts by weight of butyl acetate and this initial charge is heated to 90-160° C. The reactor is placed under pressure (1.5-6.5 bar). Thereafter, over a period of 4-7 hours, an initiator solution (50-100 parts by weight of di-tert-butyl peroxide in 50-100 parts by weight of butyl acetate) is metered in at a uniform rate under stirring. Starting 0-30 minutes after the start of the initiator feed, feed 1 consisting of ethylenically unsaturated vinylalkoxysilane monomers is metered in at a uniform rate over a period of 0.5-2 hours under stirring. Starting 0-30 minutes after the start of the initiator feed, 500-1500 parts by weight of feeds 2 to 6 consisting of styrene, methyl methacrylate and n-butyl acrylate in a weight ratio of 0.1 to 10 are metered in at a uniform rate over a period of 0.5-2 hours for each feed under stirring. After the initiator solution has been completely added (0-60 minutes after the addition of the monomer mixture has ended), the reactor is heated to 100-180° C. and stirring is continued at the specified pressure for 5-90 minutes, and then a solution consisting of 5-50 parts by weight of di-tert-butyl peroxide in 5-50 parts by weight of butyl acetate is added again over the course of 0.5-2 hours at a uniform rate. Subsequently, the batch is maintained at the specified temperature and the specified pressure for another 0.5-2 hours. Thereafter, the reaction mixture is cooled to 25-80° C. and decompressed to atmospheric pressure.
[0080] As another example, a crosslinkable silane-functional polymer is prepared as follows:
[0081] The reactor is loaded with 100-500 parts by weight of butyl acetate and this initial charge is heated to 90-160° C. The reactor is placed under pressure (1.5-6.5 bar). Thereafter, over a period of 4-7 hours, an initiator solution (50-100 parts by weight of di-tert-butyl peroxide in 50-100 parts by weight of butyl acetate) is metered in at a uniform rate under stirring. Starting 0-30 minutes after the start of the initiator feed, feed 1 consisting of ethylenically unsaturated vinylalkoxysilane monomers is metered in at a uniform rate over a period of 0.5-2 hours under stirring. Starting 0-30 minutes after the start of the initiator feed, 500-1500 parts by weight of feeds 2 to 6 consisting of styrene, methyl methacrylate and ethylhexyl acrylate in a weight ratio of 0.1 to 10 are metered in at a uniform rate over a period of 0.5-2 hours for each feed under stirring. After the initiator solution has been completely added (0-60 minutes after the addition of the monomer mixture has ended), the reactor is heated to 100-180° C. and stirring is continued at the specified pressure for 5-90 minutes, and then a solution consisting of 5-50 parts by weight of di-tert-butyl peroxide in 5-50 parts by weight of butyl acetate is added again over the course of 0.5-2 hours at a uniform rate. Subsequently, the batch is maintained at the specified temperature and the specified pressure for another 0.5-2 hours. Thereafter, the reaction mixture is cooled to 25-80° C. and decompressed to atmospheric pressure.
[0082] As a further example, a crosslinkable silane-functional polymer is prepared as follows:
[0083] The reactor is loaded with 100-500 parts by weight of Shellsol A and this initial charge is heated to 90-160° C. The reactor is placed under pressure (1.5-6.5 bar). Thereafter, over a period of 4-7 hours, an initiator solution (50-100 parts by weight of di-tert-butyl peroxide in 50-100 parts by weight of Shellsol A) is metered in at a uniform rate under stirring. Starting 0-30 minutes after the start of the initiator feed, feed 1 consisting of ethylenically unsaturated vinylalkoxysilane monomers is metered in at a uniform rate over a period of 0.5-2 hours under stirring. Starting 0-30 minutes after the start of the initiator feed, 500-1500 parts by weight of feeds 2 to 6 consisting of styrene, methyl methacrylate and hydroxypropyl methacrylate in a weight ratio of 0.1 to 10 are metered in at a uniform rate over a period of 0.5-2 hours for each feed under stirring. After complete addition of the initiator solution (0-60 minutes after the end of the addition of the monomer mixture), the reactor is heated to 100-180° C. and stirring is continued at the specified pressure for 5-90 minutes, and then a solution consisting of 5-50 parts by weight of di-tert-butyl peroxide in 5-50 parts by weight of Shellsol A is added again at a uniform rate over the course of 0.5-2 hours. Subsequently, the batch is maintained at the specified temperature and the specified pressure for a further 0.5-2 hours. Thereafter, the reaction mixture is cooled to 25-80° C. and depressurized to atmospheric pressure.
[0084] The method for synthesizing the acrylsilane polymer according to the present invention reduces monomer residues (<5%) and the obtained acrylsilane polymer has a solid content of not less than 70 wt % and a Tg of less than 15° C.
[0085] Monomers and / or unsaturated oligomers and / or unsaturated polymers
[0086] Any common monomers and their unsaturated oligomers and unsaturated polymers used for preparing coating compositions can be used herein, such as (meth)acrylates, unsaturated carboxylic acids and unsaturated alcohols. The monomers are preferably phenoxyethyl acrylate, 1,6-hexanediol diacrylate and trimethylolpropane triacrylate, and the unsaturated oligomers are polyurethane-modified acrylate oligomers, such as UA 8987, UA 19T, UA9050 and UA 9136, and polyester-modified acrylate oligomers such as PE 55F, PE 9121 and PE 9105, and the unsaturated polymer is an unsaturated polyester.
[0087] Preferably, the monomer or the unsaturated oligomer or the unsaturated polymer has a weight average molecular weight of 200 to 20,000, a hydroxyl value of 0 to 350 mg KOH / g, and an acid value of 0 to 150 mg KOH / g.
[0088] Preferably, the unsaturated polyester is prepared by condensation of at least one monounsaturated linear aliphatic dicarboxylic acid or its anhydride and at least one saturated aliphatic diol. More preferably, the unsaturated polyester is prepared by condensation of at least one monounsaturated linear aliphatic dicarboxylic acid or its anhydride selected from maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, hexahydrophthalic acid, hexahydrophthalic anhydride and fumaric acid and at least one saturated aliphatic diol selected from neopentyl glycol, 1,4 butanediol, 1,6 hexanediol and cyclohexyl dimethanol.
[0089] As an example, an unsaturated polyester is prepared as follows:
[0090] 200-500 parts by weight of trimethylolpropane (TMP), 500-1000 parts by weight of itaconic acid (IA) and 300-600 parts by weight of 1,4-butanediol (BD) are loaded into a stainless steel reactor equipped with a reflux condenser, a water separator and N2 inlet. Thereafter, 5-50 parts by weight of xylene are added as an entrainer, 0.05-0.5 parts by weight of 2,6-di-tert-butyl-4-methylphenol (BHT) as a stabilizer and 0.5-1 parts by weight of tetra-n-butyl titanate (TBT) as a catalyst. The resulting reaction mixture is heated under N2 for 2-8 hours. During the entire reaction time, the temperature of the reaction mixture does not exceed 200 ° C. After reaching an acid value of 5-100 mg KOH / g, the reaction mixture is cooled to 50-100 ° C and the polymer is diluted by adding 300-700 parts by weight of butyl acetate (BA).
[0091] As another example, an unsaturated polyester is prepared as follows:
[0092] 200-500 parts by weight of trimethylolpropane (TMP), 400-800 parts by weight of maleic anhydride (MAH) and 400-800 parts by weight of neopentyl glycol (NPG) are loaded into a stainless steel reactor equipped with a reflux condenser, a water separator and an N2 inlet. Thereafter, 5-50 parts by weight of xylene are added as an entrainer. The resulting reaction mixture is heated under N2 for 2-8 hours. During the entire reaction time, the temperature of the reaction mixture does not exceed 200°C. After reaching an acid value of 5-50 mg KOH / g, the reaction mixture is cooled to 50-100°C and the polymer is diluted by adding 300-700 parts by weight of butyl acetate (BA).
[0093] As another example, an unsaturated polyester is prepared as follows:
[0094] 200-500 parts by weight of trimethylolpropane (TMP), 400-800 parts by weight of maleic anhydride (MAH) and 400-800 parts by weight of neopentyl glycol (NPG) are loaded into a stainless steel reactor equipped with a reflux condenser, a water separator and an N2 inlet. Thereafter, 5-50 parts by weight of xylene are added as an entrainer and 0.05-0.5 parts by weight of 2,6-di-tert-butyl-4-methylphenol (BHT) are added as a stabilizer. The resulting reaction mixture is heated under N2 for 2-8 hours. During the entire reaction time, the temperature of the reaction mixture does not exceed 200°C. After reaching an acid value of 5-50 mg KOH / g, the reaction mixture is cooled to room temperature. The solid content of the resulting polymer is 95-100%.
[0095] As another example, an unsaturated polyester is prepared as follows:
[0096] 150-400 parts by weight of trimethylolpropane (TMP), 400-800 parts by weight of itaconic acid (IA) and 200-600 parts by weight of 1,4-butanediol (BD) are loaded into a stainless steel reactor equipped with a reflux condenser, a water separator and an N2 inlet. Thereafter, 5-50 parts by weight of xylene are added as an entrainer and 0.1-1 parts by weight of 4-methoxyphenol (MEHQ) are added as a stabilizer. The resulting reaction mixture is heated under N2 for 2-8 hours. During the entire reaction time, the temperature of the reaction mixture does not exceed 230°C. After reaching an acid value of 5-50 mg KOH / g, the reaction mixture is cooled to room temperature.
[0097] As a further example, an unsaturated polyester is prepared as follows:
[0098] 100-400 parts by weight of trimethylolpropane, 300-600 parts by weight of itaconic acid, 200-500 parts by weight of 1,4-butanediol, 5-50 parts by weight of xylene, 0.1-1 parts by weight of 4-methoxyphenol (MEHQ) and 1-5 parts by weight of 2,6-di-tert-butyl-4-methylphenol (BHT) are placed in a reactor and heated to 50-150° C. and maintained for 0.5-2 hours. The temperature is increased to 100-200° C. and maintained for another hour, then increased to 220-260° C. and maintained for 1-4 hours. Xylene is distilled off during the reaction. Cool to 50-100° C. and add 200-400 parts by weight of hexahydrophthalic anhydride, 0.05-0.5 parts by weight of 2,6-di-tert-butyl-4-methylphenol (BHT) and 0.05-0.5 parts by weight of 4-methoxyphenol (MEHQ) to the mixture and heat to 120-180° C. for several hours. 400-800 parts by weight of Cadura E10P, 0.05-0.5 parts by weight of 2,6-di-tert-butyl-4-methylphenol (BHT) and 0.05-0.5 parts by weight of 4-methoxyphenol (MEHQ) are added to the reaction mixture over 0.5-3 hours and cooled to 25-80° C. and further add 300-700 parts by weight of trimethylolpropane triacrylate and 300-700 parts by weight of 1,6-hexanediol diacrylate.
[0099] The obtained unsaturated polyester has a solid content of not less than 65% by weight and a Tg of less than 100°C.
[0100] Initiators and catalysts
[0101] Any initiator commonly used in free radical polymerization, such as dibenzoyl peroxide (BPO), azobisisobutyronitrile, ethyl 2-oxocyclopentanecarboxylate (EOC) and benzopinacol (BP), can be used herein.
[0102] Any catalyst commonly used for silane condensation may be used herein, such as phenyl acid phosphate (PAP), amine neutralized p-toluenesulfonic acid (NARCURE 2500), and amine neutralized phosphate ester (NARCURE 4575).
[0103] Dual reactive coating compositions
[0104] The dual reactive coating composition is prepared by mixing the following components
[0105] a). 24 to 90% by weight of crosslinkable silane-functional monomers and / or oligomers and / or polymers;
[0106] b). 9 to 75% by weight of one monomer and / or unsaturated oligomer and / or unsaturated polymer;
[0107] c) 0.5 wt % to 10 wt % of an initiator; and
[0108] d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition.
[0109] Preferably, the dual reactive coating composition is prepared by mixing the following components
[0110] a). 24 to 90% by weight of crosslinkable silane-functional monomers and / or oligomers and / or polymers;
[0111] b). 9 to 75% by weight of unsaturated polyesters and / or polyester-modified oligomers;
[0112] c) 0.5 wt % to 10 wt % of an initiator; and
[0113] d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition.
[0114] More preferably, the dual reactive coating composition is prepared by mixing the following components
[0115] a). 24 to 90% by weight of a crosslinkable silane-functional polymer;
[0116] b). 9 to 75% by weight of unsaturated polyester;
[0117] c) 0.5 wt % to 10 wt % of an initiator; and
[0118] d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition.
[0119] As an example, a dual reactive coating composition is prepared by mixing 24 to 90 wt % of an acryl silane polymer and 9 to 75 wt % of an unsaturated polyester with 0.5 to 10 wt % of an initiator selected from dibenzoyl peroxide (BPO), ethyl 2-oxocyclopentanecarboxylate (EOC) or benzopinacol (BP) and 0.5 to 10 wt % of a catalyst benzoic acid phosphate (PAP, IsleChem, LLC), diluting with butyl acetate to obtain a solid content of 50 wt % and stirring until a homogeneous mixture is obtained.
[0120] As another example, a dual reactive coating composition is prepared by mixing 49 to 85 wt % of an acryl silane polymer and 14 to 50 wt % of an unsaturated polyester with 0.5 to 5 wt % of an initiator selected from dibenzoyl peroxide (BPO), ethyl 2-oxocyclopentanecarboxylate (EOC) or benzopinacol (BP) and 0.5 to 5 wt % of a catalyst benzoic acid phosphate (PAP, IsleChem, LLC), diluting with butyl acetate to obtain a solid content of 50 wt % and stirring until a homogeneous mixture is obtained.
[0121] As another example, a dual reactive coating composition is prepared by mixing 24 to 90 wt % of an acryl silane polymer and 9 to 75 wt % of a polyurethane and / or polyester modified acrylate oligomer with 0.5 to 10 wt % of an initiator selected from dibenzoyl peroxide (BPO), ethyl 2-oxocyclopentanecarboxylate (EOC) or benzopinacol (BP) and 0.5 to 10 wt % of a catalyst benzoic acid phosphate (PAP, IsleChem, LLC), diluting with butyl acetate to obtain a solid content of 50 wt % and stirring until a homogeneous mixture is obtained.
[0122] As another example, a dual reactive coating composition is prepared by mixing 49 to 85 wt % of an acryl silane polymer and 14 to 50 wt % of a polyester modified acrylate oligomer with 0.5 to 5 wt % of an initiator selected from dibenzoyl peroxide (BPO), ethyl 2-oxocyclopentanecarboxylate (EOC) or benzopinacol (BP) and 0.5 to 5 wt % of a catalyst benzoic acid phosphate (PAP, IsleChem, LLC), diluting with butyl acetate to obtain a solid content of 50 wt % and stirring until a homogeneous mixture is obtained.
[0123] As another example, a dual reactive coating composition is prepared by mixing 24 to 90 wt % of an acryl silane polymer and 9 to 75 wt % of a (meth)acrylate monomer selected from phenoxyethyl acrylate, 1,6-hexanediol diacrylate or trimethylolpropane triacrylate with 0.5 to 10 wt % of an initiator selected from dibenzoyl peroxide (BPO), ethyl 2-oxocyclopentanecarboxylate (EOC) or benzopinacol (BP) and 0.5 to 10 wt % of a catalyst benzoic acid phosphate (PAP, IsleChem, LLC), diluting with butyl acetate to obtain a solid content of 50 wt % and stirring until a homogeneous mixture is obtained.
[0124] As a further example, a dual reactive coating composition is prepared by mixing 49 to 85 wt % of an acryl silane polymer and 14 to 50 wt % of a (meth)acrylate monomer selected from phenoxyethyl acrylate, 1,6-hexanediol diacrylate or trimethylolpropane triacrylate with 0.5 to 5 wt % of an initiator selected from dibenzoyl peroxide (BPO), ethyl 2-oxocyclopentanecarboxylate (EOC) or benzopinacol (BP) and 0.5 to 5 wt % of a catalyst benzoic acid phosphate (PAP, IsleChem, LLC), diluting with butyl acetate to obtain a solid content of 50 wt % and stirring until a homogeneous mixture is obtained.
[0125] The mixture was applied to a tin test plate by knife coating to obtain a wet film thickness of 200 μm and placed at 140° C. for 20 minutes to obtain a surface dry film of about 35-55 μm. After 3 days of post-curing, a single layer test for performance inspection was carried out by evaluating hardness (K-pendulum), crosslinking performance (MEK rub test), gel content and cracking performance (bend test). The test results showed no cracking in the bend test, 60 to 140 in the K-pendulum test, and 200 to 500 in the MEK rub test.
[0126] The resulting dual-reactive coating composition is able to achieve balanced properties of flexibility and hardness and completely suppress brittleness and cracking of topcoats or clearcoats.
[0127] Roll-to-roll coating composition
[0128] Based on the dual-reactive coating composition, it can be prepared by adding a reactive diluent, such as phenoxyethyl acrylate ( POEA), 1,6-hexanediol diacrylate and / or trimethylolpropane triacrylate and additives such as The roll-to-roll coating composition is prepared by the method of claim 1. The solid content of the roll-to-roll coating composition is not less than 90 wt %, preferably not less than 95 wt %.
[0129] As an example, a roll-to-roll coating composition is prepared as follows: 40 wt % to 60 wt % of an aliphatic urethane acrylate resin ( UA 8987), 10 wt % to 30 wt % of polyester modified acrylate oligomer ( PE 55F), 9 wt % to 50 wt % of an unsaturated silane functional monomer (3-methacryloxypropyltrimethoxysilane), 19.5 wt % to 39.5 wt % of an acrylate-based reactive diluent (1,6-hexanediol diacrylate, HDDA), 0.5 wt % to 10 wt % of a catalyst (Narcure 2500, King Industries), 0.5 wt % to 10 wt % of an initiator (benzopinacol, BP) and 0.5 wt % to 10 wt % of an additive wetting agent (Hydropalat WE3220) were uniformly mixed to obtain a roll-to-roll coating composition.
[0130] The coating composition was coated on a tin plate using an Erichsen rod coater and placed at 140°C for 20 minutes. After 3 days of post-curing, a single-layer test for performance examination was conducted by evaluating hardness (Koenig pendulum), crosslink density (MEK double rub test), cupping performance (Erichson cupping), and gloss and haze measurement (specular reflection). The results showed that the resulting roll-to-roll coating composition can provide high solid content, excellent high crosslinking performance, good appearance and cupping (Erichson index, EI).
[0131] 1K varnish composition
[0132] Based on the dual-reactive coating composition, it can be prepared by adding a reactive diluent, such as phenoxyethyl acrylate ( POEA), 1,6-hexanediol diacrylate and / or trimethylolpropane triacrylate, additives such as BYK 3190 and cosolvents such as 1-butanol to prepare a 1K varnish composition. The VOC of the obtained varnish composition is not more than 420 g / L, preferably not more than 350 g / L.
[0133] As an example, a 1K varnish composition is prepared as follows: 10 wt % to 60 wt % of an acrylate / styrene resin having a silane functional group, 10 wt % to 60 wt % of an unsaturated polyester resin, 19.5 wt % to 69.5 wt % of an acrylate-based reactive diluent (trimethylolpropane triacrylate, TMPTA), 4 wt % to 10 wt % of a silane-based sagging control agent (SCA), 1 wt % to 10 wt % of a catalyst (Narcure 4575, King Industries), 0.4 wt % to 10 wt % of an initiator (benzopinacol, BP), 5 wt % to 20 wt % of a cosolvent (1-butanol), and 0.1 wt % to 2 wt % of an additive leveling agent (BYK 3190) are uniformly mixed to obtain a 1K varnish composition. The coating composition exhibits thixotropic behavior, with a ratio of low / high shear viscosity of η2 (shear rate = 1 s-1) / η1 (shear rate = 1000 s-1) > 8. The VOC value of the coating composition has been measured to be 325 g / L, which is a substantial reduction in VOC content compared to conventional 1K coating compositions (VOC = 450-550 g / L).
[0134] The composition was sprayed on a black basecoat coated tin plate and placed at 140°C for 20 minutes. After 3 days of post-curing, a single layer test for performance inspection was conducted by evaluating hardness (Koenig pendulum), crosslink density (MEK double rub test), base and acid corrosion resistance, cupping performance (Erichson cupping), appearance (wave scan), and gloss and haze measurement (specular reflection). The results show that the resulting 1K varnish composition can provide high solid content and low VOC value, excellent high crosslinking performance, good appearance, cupping (Erichson index, EI), and acid and base corrosion resistance.
[0135] Implementation
[0136] A first embodiment is a dual reactive coating composition comprising
[0137] a). 24 to 90% by weight of crosslinkable silane-functional monomers and / or oligomers and / or polymers;
[0138] b). 9 to 75% by weight of one monomer and / or unsaturated oligomer and / or unsaturated polymer;
[0139] c) 0.5 wt % to 10 wt % of an initiator; and
[0140] d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition.
[0141] A second embodiment is a dual reactive coating composition comprising
[0142] a). 24 to 90% by weight of crosslinkable silane-functional monomers and / or oligomers and / or polymers;
[0143] b). 9 to 75% by weight of unsaturated polyester and / or polyurethane modified oligomers and / or polyester modified oligomers;
[0144] c) 0.5 wt % to 10 wt % of an initiator; and
[0145] d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition.
[0146] A third embodiment is a dual reactive coating composition comprising
[0147] a). 24 to 90% by weight of a crosslinkable silane-functional polymer;
[0148] b). 9 to 75% by weight of unsaturated polyester;
[0149] c) 0.5 wt % to 10 wt % of an initiator; and
[0150] d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition.
[0151] A fourth embodiment is a dual reactive coating composition according to any one of embodiments 1 to 3, wherein the crosslinkable silane functional polymer is prepared by polymerization of a monomer comprising
[0152] i) 20 to 50 wt% of a vinylalkoxysilane of formula I
[0153] H2C=CH-(CH2) n -Si-(R1) m (R2) 3-m
[0154] wherein R1 is an aryl or alkyl group having C1-C6, R2 is an alkoxy group having C1-C6, m is 0 or 1, and n is an integer from 0 to 3;
[0155] ii) 50 to 80 wt% of (meth)acrylate monomers; and
[0156] iii) 0 wt% to 30 wt% of a styrenic monomer, all weight percentages based on the total weight of the silane-functional polymer.
[0157] A fifth embodiment is a dual reactive coating composition according to any one of embodiments 1 to 4, wherein the crosslinkable silane functional polymer is prepared by polymerization of a monomer comprising
[0158] i) 20 to 50% by weight of vinyltrimethoxysilane;
[0159] ii) 50 to 80 wt% of at least one (meth)acrylate monomer selected from methyl methacrylate, n-butyl acrylate, ethylhexyl acrylate and hydroxypropyl methacrylate; and
[0160] iii) 0 wt % to 30 wt % styrene, all weight percentages based on the total weight of the silane-functional polymer.
[0161] A sixth embodiment is a dual reactive coating composition according to any one of embodiments 1 to 5, wherein the crosslinkable silane functional oligomer or polymer has a weight average molecular weight of less than 30,000, preferably less than 20,000.
[0162] A seventh embodiment is a dual reactive coating composition according to any one of embodiments 1 to 6, wherein the crosslinkable silane functional polymer has a hydroxyl value of 0 to 150 mg KOH / g and an acid value of 0 to 50 mg KOH / g.
[0163] The eighth embodiment is a dual reactive coating composition according to any one of embodiments 1 and 4 to 7, wherein the monomer or unsaturated oligomer or unsaturated polymer has a weight average molecular weight of 200 to 20,000.
[0164] The ninth embodiment is a dual reactive coating composition according to any one of embodiments 1 and 4 to 8, wherein the monomer or unsaturated oligomer or unsaturated polymer has a hydroxyl value of 0 to 350 mg KOH / g and an acid value of 0 to 150 mg KOH / g.
[0165] The tenth embodiment is a dual reactive coating composition according to any one of embodiments 2 to 3, wherein the unsaturated polyester is prepared by the condensation of at least one monounsaturated linear aliphatic dicarboxylic acid or its anhydride and at least one saturated aliphatic diol.
[0166] The eleventh embodiment is a dual reactive coating composition according to embodiment 10, wherein the unsaturated polyester is prepared by the condensation of at least one monounsaturated linear aliphatic dicarboxylic acid or its anhydride selected from maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, hexahydrophthalic acid, hexahydrophthalic anhydride and fumaric acid and at least one saturated aliphatic diol selected from neopentyl glycol, 1,4 butanediol, 1,6 hexanediol and cyclohexanedimethanol.
[0167] The twelfth embodiment is a dual reactive coating composition according to any one of embodiments 1 to 11, wherein the initiator is at least selected from dibenzoyl peroxide (BPO), ethyl 2-oxocyclopentanecarboxylate (EOC) and benzopinacol (BP).
[0168] The thirteenth embodiment is a dual reactive coating composition according to any one of embodiments 1 to 12, wherein the catalyst is at least selected from benzoic acid phosphate (PAP), amine neutralized p-toluenesulfonic acid (NARCURE 2500) and amine neutralized phosphate (NARCURE 4575).
[0169] A fourteenth embodiment is a dual reactive coating composition according to any one of embodiments 1 to 13, wherein the crosslinkable silane functional polymer is prepared by a method comprising two steps: in a first step, a vinyl alkoxysilane monomer, a (meth)acrylate monomer, and optionally a styrenic monomer and an initiator are mixed with an organic solvent and heated, and in a second step, the (meth)acrylate monomer, optionally a styrenic monomer and an initiator are added, wherein in the second step, the (meth)acrylate monomer and optionally a styrenic monomer are added in not less than two batches, and the time between each batch is not less than half an hour and the weight ratio between the (meth)acrylate monomer and the optional styrenic monomer added in each batch is 1:15 to 15:1.
[0170] A fifteenth embodiment is a dual reactive coating composition according to any one of embodiments 1 to 14, wherein it further comprises a silane functional sag control agent.
[0171] The sixteenth embodiment is a film obtained by curing and drying the dual reactive coating composition according to any one of embodiments 1 to 15.
[0172] A seventeenth embodiment is a substrate coated with the dual reactive coating composition according to any one of embodiments 1 to 15.
[0173] An eighteenth embodiment is a substrate according to embodiment 17, wherein the substrate is a car or a truck.
[0174] A nineteenth embodiment is a method for preparing a dual reactive coating composition according to claim 1 by mixing the following components
[0175] a). 24 to 90% by weight of crosslinkable silane-functional monomers and / or oligomers and / or polymers;
[0176] b). 9 to 75% by weight of one monomer and / or unsaturated oligomer and / or unsaturated polymer;
[0177] c) 0.5 wt % to 10 wt % of an initiator; and
[0178] d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition.
[0179] The twentieth embodiment is a method for preparing the dual reactive coating composition according to embodiment 2 by mixing the following components:
[0180] a). 24 to 90% by weight of crosslinkable silane-functional monomers and / or oligomers and / or polymers;
[0181] b). 9 to 75% by weight of unsaturated polyester and / or polyurethane modified oligomers and / or polyester modified oligomers;
[0182] c) 0.5 wt % to 10 wt % of an initiator; and
[0183] d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition.
[0184] The twenty-first embodiment is a method for preparing the dual reactive coating composition according to embodiment 3 by mixing the following components:
[0185] a). 24 to 90% by weight of a crosslinkable silane-functional polymer;
[0186] b). 9 to 75% by weight of unsaturated polyester;
[0187] c) 0.5 wt % to 10 wt % of an initiator; and
[0188] d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition.
[0189] The twenty-second embodiment is a roll-to-roll coating composition comprising the dual reactive coating composition according to any one of embodiments 1 to 15, a reactive diluent and an additive, wherein the solid content of the resulting roll-to-roll coating composition is not less than 90 wt %, preferably not less than 95 wt %.
[0190] The twenty-third embodiment is a 1K varnish composition comprising the dual reactive coating composition according to any one of embodiments 1 to 15, a reactive diluent, an additive and a cosolvent, wherein the VOC of the resulting varnish composition is no greater than 420 g / L, preferably no greater than 350 g / L. Example
[0191] The invention will now be described with reference to examples, which are not intended to limit the invention.
[0192] Example 1-3: Preparation of Acrylate Polymer Containing Vinyl Silane
[0193] The reactor was loaded with 378 parts by weight of Shellsol A and this initial charge was heated to 145° C. The reactor was placed under pressure (3.5 bar). Thereafter, over a period of 5.38 hours, an initiator solution (82.9 parts by weight of di-tert-butyl peroxide in 68.6 parts by weight of Shellsol A) was metered in at a uniform rate with stirring. Starting 15 minutes after the start of the initiator feed, feed 1 consisting of VTMS was metered in at a uniform rate over a period of 1 hour with stirring. Starting 15 minutes after the start of the initiator feed, feeds 2-a to 2-e consisting of methyl methacrylate and n-butyl acrylate having the compositions listed in Table 1 below were metered in at a uniform rate over a period of 1 hour for each feed with stirring. After complete addition of the initiator solution (0.15 hours after the end of the addition of the monomer mixture), the reactor was heated to 155° C. and stirring was continued at the specified pressure for 45 minutes, and then a solution consisting of 27 parts by weight of di-tert-butyl peroxide in 22.4 parts by weight of Shellsol A was added again over the course of 1.2 hours at a uniform rate. Subsequently, the batch was kept at the specified temperature and the specified pressure for a further 1.1 hours. Thereafter, the reaction mixture was cooled to 60° C. and decompressed to atmospheric pressure. The solids content, number average molecular weight, glass transition temperature and monomer residues of the resulting copolymer solutions are given below in Table 2.
[0194] Table 1:
[0195]
[0196] Table 2:
[0197]
[0198] Example 4-13: Preparation of Acrylate / Styrene Copolymer Containing Vinyl Silane
[0199] The reactor was loaded with 378 parts by weight of Shellsol A and this initial charge was heated to 145° C. The reactor was placed under pressure (3.5 bar). Thereafter, over a period of 5.38 hours, an initiator solution (82.9 parts by weight of di-tert-butyl peroxide in 68.6 parts by weight of Shellsol A) was metered in at a uniform rate with stirring. Starting 15 minutes after the start of the initiator feed, feed 1 consisting of VTMS was metered in at a uniform rate over a period of 1 hour with stirring. Starting 15 minutes after the start of the initiator feed, feeds 3-a to 3-e consisting of styrene, methyl methacrylate and n-butyl acrylate having the compositions listed in Table 3 below were metered in at a uniform rate over a period of 1 hour for each feed. After complete addition of the initiator solution (0.15 hours after the end of the addition of the monomer mixture), the reactor was heated to 155° C. and stirring was continued at the specified pressure for 45 minutes, and then a solution consisting of 27 parts by weight of di-tert-butyl peroxide in 22.4 parts by weight of Shellsol A was added again over the course of 1.2 hours at a uniform rate. Subsequently, the batch was kept at the specified temperature and the specified pressure for a further 1.1 hours. Thereafter, the reaction mixture was cooled to 60° C. and decompressed to atmospheric pressure. The solids content, number average molecular weight, glass transition temperature and monomer residues of the resulting copolymer solutions are given below in Table 4.
[0200]
[0201]
[0202] Examples 14-15: Preparation of Acrylate / Styrene / Ethylhexyl Acrylate Copolymer Containing Vinyl Silane
[0203] The reactor was loaded with 378 parts by weight of Shellsol A and this initial charge was heated to 145° C. The reactor was placed under pressure (3.5 bar). Thereafter, over a period of 5.38 hours, an initiator solution (82.9 parts by weight of di-tert-butyl peroxide in 68.6 parts by weight of Shellsol A) was metered in at a uniform rate with stirring. Starting 15 minutes after the start of the initiator feed, feed 1 consisting of VTMS was metered in at a uniform rate over a period of 1 hour with stirring. Starting 15 minutes after the start of the initiator feed, feeds 4-a to 4-e consisting of styrene, methyl methacrylate and ethylhexyl acrylate having the compositions listed in Table 5 below were metered in at a uniform rate over a period of 1 hour for each feed. After complete addition of the initiator solution (0.15 hours after the end of the addition of the monomer mixture), the reactor was heated to 155° C. and stirring was continued at the specified pressure for 45 minutes, and then a solution consisting of 27 parts by weight of di-tert-butyl peroxide in 22.4 parts by weight of Shellsol A was added again over the course of 1.2 hours at a uniform rate. Subsequently, the batch was kept at the specified temperature and the specified pressure for a further 1.1 hours. Thereafter, the reaction mixture was cooled to 60° C. and decompressed to atmospheric pressure. The solids content, number average molecular weight, glass transition temperature and monomer residues of the resulting copolymer solutions are given below in Table 6.
[0204] Table 5:
[0205]
[0206]
[0207] Table 6:
[0208]
[0209] Example 16: Preparation of Vinylsilane-Containing Acrylate Polymer in Butyl Acetate
[0210] The reactor is loaded with 378 parts by weight of butyl acetate and this initial charge is heated to 145° C. The reactor is placed under pressure (3.5 bar). Thereafter, over a period of 5.38 hours, an initiator solution (82.9 parts by weight of di-tert-butyl peroxide in 68.6 parts by weight of butyl acetate) is metered in at a uniform rate under stirring. 15 minutes after the start of the initiator feed, 659.2 parts by weight of VTMS are metered in at a uniform rate under stirring over a period of 1 hour. In a first step, a monomer mixture consisting of 91.2 parts by weight of methyl methacrylate and 91.2 parts by weight of n-butyl acrylate is metered in simultaneously over a period of 1 hour at a uniform rate under stirring. In a second step, a monomer mixture consisting of 167.8 parts by weight of methyl methacrylate and 167.8 parts by weight of n-butyl acrylate is metered in at a uniform rate under stirring over a period of 1 hour. In the third step, a monomer mixture consisting of 102 parts by weight of methyl methacrylate and 102 parts by weight of n-butyl acrylate was metered in at a uniform rate over a period of 1 hour with stirring. In the fourth step, a monomer mixture consisting of 74 parts by weight of methyl methacrylate and 74 parts by weight of n-butyl acrylate was metered in at a uniform rate over a period of 1 hour with stirring. In the fifth step, a monomer mixture consisting of 59.4 parts by weight of methyl methacrylate and 59.4 parts by weight of n-butyl acrylate was metered in at a uniform rate over a period of 1 hour with stirring. After complete addition of the initiator solution (0.15 hours after the end of the addition of the monomer mixture), the reactor was heated to 155° C. and stirred at the specified pressure for 45 minutes, and then a solution consisting of 27 parts by weight of di-tert-butyl peroxide in 22.4 parts by weight of butyl acetate was added again over the course of 1.2 hours at a uniform rate. Subsequently, the batch was kept at the specified temperature and the specified pressure for a further 1.1 hours. Thereafter, the reaction mixture was cooled to 60° C. and decompressed to atmospheric pressure. The solid content of the obtained copolymer solution was 73.0%. The copolymer had a weight average molecular weight of 5002 g / mol. The glass transition temperature of the copolymer was -21.0° C. The monomer residues of methyl methacrylate, n-butyl acrylate and vinyl trimethoxysilane were 0.03%, <0.01% and 0.26%, respectively.
[0211] Examples 17-19: Preparation of Acrylate / Styrene Copolymers Containing Vinyl Silane in Butyl Acetate
[0212] The reactor was loaded with 378 parts by weight of butyl acetate and this initial charge was heated to 145° C. The reactor was placed under pressure (3.5 bar). Thereafter, over a period of 5.38 hours, an initiator solution (82.9 parts by weight of di-tert-butyl peroxide in 68.6 parts by weight of butyl acetate) was metered in at a uniform rate with stirring. Starting 15 minutes after the start of the initiator feed, feed 1 consisting of VTMS was metered in at a uniform rate over a period of 1 hour with stirring. Starting 15 minutes after the start of the initiator feed, feeds 3-f to 3-j consisting of styrene, methyl methacrylate and n-butyl acrylate having the compositions listed in Table 7 below were metered in at a uniform rate over a period of 1 hour for each feed. After the initiator solution was completely added (0.15 hours after the addition of the monomer mixture was completed), the reactor was heated to 155° C. and stirred at the specified pressure for 45 minutes, and then a solution consisting of 27 parts by weight of di-tert-butyl peroxide in 22.4 parts by weight of butyl acetate was added again over the course of 1.2 hours at a uniform rate. Subsequently, the batch was kept at the specified temperature and specified pressure for another 1.1 hours. Thereafter, the reaction mixture was cooled to 60° C. and decompressed to atmospheric pressure. The solid content, number average molecular weight, glass transition temperature, and monomer residues of the resulting copolymer solution are given below in Table 8.
[0213] Table 7:
[0214]
[0215] Table 8:
[0216]
[0217] Examples 20-21: Preparation of Acrylate / Styrene / Ethyl Acrylate Containing Vinylsilane in Butyl Acetate Hexyl ester copolymer
[0218] The reactor was loaded with 378 parts by weight of butyl acetate and this initial charge was heated to 145° C. The reactor was placed under pressure (3.5 bar). Thereafter, over a period of 5.38 hours, an initiator solution (82.9 parts by weight of di-tert-butyl peroxide in 68.6 parts by weight of butyl acetate) was metered in at a uniform rate with stirring. Starting 15 minutes after the start of the initiator feed, feed 1 consisting of VTMS was metered in at a uniform rate over a period of 1 hour with stirring. Starting 15 minutes after the start of the initiator feed, feeds 4-a to 4-e consisting of styrene, methyl methacrylate and ethylhexyl acrylate having the compositions listed in Table 9 below were metered in at a uniform rate over a period of 1 hour for each feed with stirring. After the initiator solution was completely added (0.15 hours after the addition of the monomer mixture was completed), the reactor was heated to 155° C. and stirred at the specified pressure for 45 minutes, and then a solution consisting of 27 parts by weight of di-tert-butyl peroxide in 22.4 parts by weight of butyl acetate was added again over the course of 1.2 hours at a uniform rate. Subsequently, the batch was kept at the specified temperature and specified pressure for another 1.1 hours. Thereafter, the reaction mixture was cooled to 60° C. and decompressed to atmospheric pressure. The solid content, number average molecular weight, glass transition temperature, and monomer residues of the resulting copolymer solution are given below in Table 10.
[0219] Table 9:
[0220]
[0221]
[0222] Table 10:
[0223]
[0224] Examples 22-23: Preparation of Acrylate / Styrene / Hydroxy-Functional Acrylate Copolymers Containing Vinyl Silane Preparation
[0225] The reactor was loaded with 378 parts by weight of Shellsol A and this initial charge was heated to 145° C. The reactor was placed under pressure (3.5 bar). Thereafter, over a period of 5.38 hours, an initiator solution (82.9 parts by weight of di-tert-butyl peroxide in 68.6 parts by weight of Shellsol A) was metered in at a uniform rate with stirring. Starting 15 minutes after the start of the initiator feed, feed 1 consisting of VTMS was metered in at a uniform rate over a period of 1 hour with stirring. Starting 15 minutes after the start of the initiator feed, feeds 5-a to 5-e consisting of styrene, methyl methacrylate and hydroxypropyl methacrylate having the compositions listed in Table 11 below were metered in at a uniform rate over a period of 1 hour for each feed. After complete addition of the initiator solution (0.15 hours after the end of the addition of the monomer mixture), the reactor was heated to 155° C. and stirring was continued at the specified pressure for 45 minutes, and then a solution consisting of 27 parts by weight of di-tert-butyl peroxide in 22.4 parts by weight of Shellsol A was added again over the course of 1.2 hours at a uniform rate. Subsequently, the batch was kept at the specified temperature and the specified pressure for a further 1.1 hours. Thereafter, the reaction mixture was cooled to 60° C. and decompressed to atmospheric pressure. The solids content, number average molecular weight, glass transition temperature and monomer residues of the resulting copolymer solutions are given below in Table 12.
[0226] Table 11:
[0227]
[0228] Table 12:
[0229]
[0230] Example 24: Unsaturated polyester based on itaconic acid in butyl acetate
[0231] 342.3 parts by weight of trimethylolpropane (TMP), 819.2 parts by weight of itaconic acid (IA) and 536.2 parts by weight of 1,4-butanediol (BD) are loaded into a stainless steel reactor equipped with a reflux condenser, a water separator and an N2 inlet. Thereafter, 20 parts by weight of xylene are added as an entrainer, 0.252 parts by weight of 2,6-di-tert-butyl-4-methylphenol (BHT) as a stabilizer and 0.756 parts by weight of tetra-n-butyl titanate (TBT) as a catalyst. The resulting reaction mixture is heated under N2 for 5 hours. During the entire reaction time, the temperature of the reaction mixture does not exceed 200°C. After reaching an acid value of 52mg KOH / g, the reaction mixture is cooled to 80°C and the polymer is diluted by adding 580.4 parts by weight of butyl acetate (BA). The solid content of the resulting polymer solution is 69.03%. The obtained unsaturated polyester had a number average molecular weight of 509 g / mol, a weight average molecular weight of 1260 g / mol, an OH value of 301.7 mg KOH / g and a glass transition temperature of 65.9°C.
[0232] Example 25: Unsaturated polyester based on maleic anhydride in butyl acetate
[0233] 341.3 parts by weight of trimethylolpropane (TMP), 615.7 parts by weight of maleic anhydride (MAH) and 618 parts by weight of neopentyl glycol (NPG) were loaded into a stainless steel reactor equipped with a reflux condenser, a water separator and an N2 inlet. Thereafter, 20 parts by weight of xylene were added as an entrainer. The resulting reaction mixture was heated under N2 for 4 hours. During the entire reaction time, the temperature of the reaction mixture did not exceed 200°C. After reaching an acid value of 12 mg KOH / g, the reaction mixture was cooled to 80°C and the polymer was diluted by adding 525 parts by weight of butyl acetate (BA). The solid content of the resulting polymer solution was 69.00%. The resulting unsaturated polyester had a number average molecular weight of 801 g / mol, a weight average molecular weight of 2047 g / mol, an OH value of 272.2 mgKOH / g and a glass transition temperature of 0.6°C.
[0234] Example 26: Unsaturated polyester based on maleic anhydride
[0235] 341.3 parts by weight of trimethylolpropane (TMP), 615.7 parts by weight of maleic anhydride (MAH) and 618 parts by weight of neopentyl glycol (NPG) were loaded into a stainless steel reactor equipped with a reflux condenser, a water separator and an N2 inlet. Thereafter, 20 parts by weight of xylene were added as an entrainer and 0.158 parts by weight of 2,6-di-tert-butyl-4-methylphenol (BHT) as a stabilizer. The resulting reaction mixture was heated under N2 for 4 hours. During the entire reaction time, the temperature of the reaction mixture did not exceed 200°C. After reaching an acid value of 17 mg KOH / g, the reaction mixture was cooled to room temperature. The solid content of the resulting polymer solution was 100%. The resulting unsaturated polyester had a number average molecular weight of 805 g / mol, a weight average molecular weight of 1937 g / mol, an OH value of 264.4 mg KOH / g and a glass transition temperature of -14.0°C.
[0236] Example 27: Unsaturated polyester based on maleic anhydride in reactive diluent
[0237] 1595.2 parts by weight of Example 23 were loaded into a stainless steel reactor equipped with a reflux condenser, a water separator and an N2 inlet and heated to 80°C. Thereafter, the polymer was diluted by adding 262 parts by weight of hexanediol diacrylate (HDDA) and 262 parts by weight of trimethylolpropane triacrylate (TMPTA). The solid content of the resulting polymer solution was 75.00%. The resulting unsaturated polyester had a number average molecular weight of 805 g / mol, a weight average molecular weight of 1937 g / mol, an OH value of 256.6 mgKOH / g and a glass transition temperature of -14.0°C.
[0238] Example 28: Unsaturated polyester based on itaconic acid
[0239] 273.8 parts by weight of trimethylolpropane (TMP), 655.3 parts by weight of itaconic acid (IA) and 429.0 parts by weight of 1,4-butanediol (BD) were loaded into a stainless steel reactor equipped with a reflux condenser, a water separator and an N2 inlet. Thereafter, 16 parts by weight of xylene were added as an entrainer and 0.4 parts by weight of 4-methoxyphenol (MEHQ) as a stabilizer. The resulting reaction mixture was heated under N2 for 4 hours. During the entire reaction time, the temperature of the reaction mixture did not exceed 230°C. After reaching an acid value of 43mg KOH / g, the reaction mixture was cooled to room temperature. The solid content of the resulting polymer was 100.00%. The resulting unsaturated polyester had a number average molecular weight of 907g / mol, a weight average molecular weight of 2030g / mol, an OH value of 255.6mg KOH / g and a glass transition temperature of 9.6°C.
[0240] Example 29: Unsaturated polyester based on itaconic acid in reactive diluent
[0241] 1374.5 parts by weight of the unsaturated polyester obtained from Example 28 were loaded into a stainless steel reactor equipped with a reflux condenser, a water separator and an N2 inlet and heated to 80°C. Thereafter, the polymer was diluted by adding 363 parts by weight of hexanediol diacrylate (HDDA) and 363 parts by weight of trimethylolpropane triacrylate (TMPTA). The solid content of the resulting polymer solution was 65.00%. The resulting unsaturated polyester had a number average molecular weight of 805 g / mol, a weight average molecular weight of 1937 g / mol, an OH value of 248.3 mg KOH / g and a glass transition temperature of 9.6°C.
[0242] Example 30: Hydrophobically modified itaconic acid and hexahydrophthalic anhydride in a reactive diluent Unsaturated polyester
[0243] 210 g of trimethylolpropane, 503 g of itaconic acid, 329 g of 1,4-butanediol, 12 g of xylene, 0.5 g of MEHQ and 1.5 g of BHT were placed in a reactor, heated to 100°C and maintained for 1 hour. The temperature was raised to 160°C and maintained for another 1 hour, then raised to 230°C and maintained for 2 hours. Xylene was distilled off during the reaction. Cooled to 80°C and 322 g of hexahydrophthalic anhydride, 100 mg of BHT and 80 mg of MEHQ (hydroquinone monomethyl ether) were added to the mixture and heated to 140°C for several hours. 623 g of Cadura E10P, 100 mg of BHT and 80 mg of MEHQ were added to the reaction mixture over 1.5 hours, cooled to 40°C and 500 g of trimethylolpropane triacrylate and 500 g of 1,6-hexanediol diacrylate were added. The reaction yields a solvent-free, low-viscosity unsaturated polyester resin (67% in reactive diluent) having an acid value of 10-50 mg KOH / g, a hydroxyl value of 100-300 mg KOH / g and a glass transition temperature of -55°C.
[0244] Example 31: Silane-based sag control agent (12 wt% in butyl acetate)
[0245] 44.25 grams of 3-aminopropyl triethoxysilane were dissolved in 37.05 grams of butyl acetate and then placed in a 1-liter metal bucket containing 370.43 grams of butyl acetate. The solution was mixed with a dissolver at 2000 rpm for 2 minutes. Then 16.53 grams of hexamethylene diisocyanate were dissolved in 31.74 grams of butyl acetate and loaded into an automatic metering machine. The liquid in the metal bucket was stirred with a dissolver at a speed of 2000 rpm. Then the isocyanate solution was added dropwise during 20 minutes. After this step, the solution was kept in the dissolver for another 2 minutes. Total solid content 12% by weight, η1 (shear rate = 1000s -1 )=46mPa s、η2(shear rate=1s -1 )=13759mPa.s
[0246] Example 32: Silane-based sag control agent (12 wt % in butyl acetate)
[0247] 88.50 grams of 3-aminopropyl triethoxysilane was dissolved in 37.05 grams of butyl acetate and then placed in a 1-liter metal bucket containing 293.78 grams of butyl acetate. The solution was mixed with a dissolver at 2000rpm for 2 minutes. Then 33.06 grams of hexamethylene diisocyanate were dissolved in 47.61 grams of butyl acetate and loaded into an automatic metering machine. The liquid in the metal bucket was stirred with a dissolver at a speed of 2000rpm. Then the isocyanate solution was added dropwise during 30 minutes. After this step, the solution was kept in the dissolver for another 2 minutes. Total solid content 24% by weight, η1 (shear rate = 1000s -1 )=60mPa s、η2(shear rate=1s -1 )=16833mPa
[0248] Examples 33 to 50: Dual Reactive Coating Compositions
[0249] The components of Examples 33 to 50 were mixed with initiators dibenzoyl peroxide (BPO), ethyl 2-oxocyclopentanecarboxylate (EOC) or benzopinacol (BP) and a benzoic acid phosphate catalyst (PAP, IsleChem, LLC) as listed in the table below, diluted with butyl acetate to give a solid content of 50% by weight and stirred until a homogeneous mixture was obtained. The mixture was applied to a tin test plate by knife coating to give a wet film thickness of 200 nm and placed at 140° C. for 20 minutes to give a surface-dry film of about 35-55 nm. After 3 days of post-curing, a single-layer test for performance inspection was performed by evaluating hardness (K-pendulum), crosslinking properties (MEK rub test), gel content and cracking properties (bend test). The values are listed in Table 13 below. The dried and cured films of Examples 33 to 50 were obtained as surface-dry clear coatings.
[0250] Table 13:
[0251]
[0252]
[0253] Examples 51-53: Preparation and Application of Roll-to-Roll Coating Compositions
[0254] The aliphatic urethane acrylate resin ( UA 8987), polyester modified acrylate oligomer ( PE 55F, PE 9121, PE9105), unsaturated silane functional monomer (3-methacryloxypropyltrimethoxysilane), acrylate-based reactive diluent (1,6-hexanediol diacrylate, HDDA; POEA), a catalyst (Narcure 2500, King Industries), an initiator (benzopinacol, BP) and an additive wetting agent (Hydropalat WE3220) were uniformly mixed to obtain a roll-to-roll coating composition as Examples 51-53. The coating composition was coated on a tin plate using an Erichsen rod coater and placed at 140° C. for 20 minutes. After 3 days of post-curing, a single-layer test for performance inspection was performed by evaluating hardness (Koenig pendulum), crosslink density (MEK double rub test), cupping performance (Erichson cupping), and gloss and haze measurements (specular reflection). The dried and cured films of Examples 51 to 53 were obtained as surface-dried clear coatings. The values are listed in Table 14 below.
[0255] Table 14:
[0256]
[0257] Example 54: Preparation and spraying of 1K varnish composition
[0258] According to the amounts given in Table 15 below, an acrylate / styrene resin with silane functionality, an unsaturated polyester resin, an acrylate-based reactive diluent (trimethylolpropane triacrylate, TMPTA), a silane-based sag control agent (SCA), a catalyst (Narcure 4575, King Industries), an initiator (benzopinacol, BP), a cosolvent (1-butanol) and an additive leveling agent (BYK 3190) were uniformly mixed to obtain a 1K varnish composition as Example 54. The coating composition exhibited thixotropic behavior with a ratio of low / high shear viscosity of η2 (shear rate = 1 s-1) / η1 (shear rate = 1000 s-1) of >8. The VOC value of the coating composition has been determined to be 325 g / L, which is a substantial reduction in the VOC content compared to conventional 1K coating compositions (VOC = 450-550 g / L). The composition was sprayed on a black paint-coated tin plate and left at 140°C for 20 minutes. After 3 days of post-curing, a single layer test for performance inspection was conducted by evaluating hardness (Koenig pendulum), crosslink density (MEK double rub test), alkali and acid resistance, cupping performance (Erichson cupping), appearance (wave scan) and gloss and haze measurement (specular reflection). The dried and cured film of Example 62 was obtained as a surface-dried clear coat on a black paint. The values are listed in Table 15 below. It can be clearly seen from Example 54 that the technical method of the present invention can provide high solids content and low VOC values, excellent high crosslinking performance, good appearance, comparable cupping (Erichson index, EI) and better acid and alkali resistance compared to conventional 1K polyurethane or acid / epoxy varnishes.
[0259] Table 15:
[0260]
[0261]
[0262] <Resin Characterization>
[0263] The skilled person in the art knows methods for determining the acid value, OH value, epoxy equivalent, solid content and number average and weight average molecular weight. They are determined according to the following standards:
[0264] The acid number was determined in accordance with DIN EN ISO 2114 (date: June 2002). The OH number was determined in accordance with DIN 53240-2 (date: November 2007). The epoxy equivalent was determined in accordance with DIN EN ISO 3001 (date: November 1999). The solids content was determined in accordance with DIN EN ISO 3251 (date: June 2008). The number-average and weight-average molecular weights were determined in accordance with DIN 55672-1 (date: August 2007).
[0265] <Solid content>
[0266] The solid contents of the varnish compositions of Examples 51 to 54 were calculated based on the weight loss of the compositions at 130° C. for 60 minutes.
[0267] <Performance Test>
[0268] (1) Hardness
[0269] The pendulum damping test according to Koenig or Persoz is used to mechanically measure the surface hardness of a coating. The hardness of a coating is determined by the number of oscillations of the pendulum between two specified angles (6 to 3 degrees for a Koenig pendulum or 12 to 4 degrees for a Persoz pendulum). As the hardness of the coating surface increases, the number of oscillations also increases. These methods are standardized in the specification ISO 1522.
[0270] (2) Solvent friction test
[0271] In order to evaluate crosslinking and ensure that the coating system has cured, a solvent rub test is performed using methyl ethyl ketone (MEK) as a solvent. This test is widely used in the paint industry because it provides a quick relative estimate of the degree of cure without having to wait for long-term exposure results. The friction meter is a double rub (rubbing forward once and rubbing backward once constitutes a double rub), which gives a measurable value of MEK tolerance and degree of cure. The MEK double rub value of conventional 2K polyurethane or acid / epoxy varnish is about 200 times.
[0272] (3) Bending test
[0273] The bend test is used to determine the effect of bending on the elasticity, adhesion and elongation properties of cured coatings on metal plates. The conical bend tester consists of a frame with bending bars and a roller pivoted on a steel conical mandrel with a diameter of 3.2-38.1 mm. The specimen can be bent over part of the length of the mandrel or along the entire length of the mandrel, and the results (cracks) corresponding to different test diameters can be observed in a single operation.
[0274] (4) VOC test
[0275] To determine the emission of volatile organic compounds (VOCs) from the coating composition, a gravimetric method was used. The VOC content was measured based on the weight loss of the composition when heated to 105° C. for 60 minutes.
[0276] (5) Rheological test
[0277] The thixotropic effect of the sag control agent and the coating composition was characterized using an Anton Paar rheometer. The 2D rheological behavior was measured by rapid shear rate changes. The test consisted of a flow test with two different shear rates (shear rate 1 = 1 s -1 , shear rate 2 = 1000s -1 The thixotropic index is defined as the ratio between the viscosity of a sample under high shear (η2) and low shear (η1).
[0278] (6) Cupping test
[0279] Erichsen cupping is used to evaluate flexibility by testing the coating's resistance to damage. The test uses a 20 mm diameter hemispherical punch to slowly stretch a dried and cured coating on a metal plate at room temperature. The test is run until damage to the coating is observed, and the depth of the indentation at damage (in mm) is expressed as the Erichsen Index IE. The IE for conventional coatings is >5 mm.
[0280] (7) Appearance
[0281] The appearance of a dried and cured coating is evaluated by its surface texture, which is measured by a BYK wave-scan dual. The surface texture is a mixture of various textures, from very fine to very rough. BYK wave-scan dual measures the surface texture at different scale levels, which are distinguished into six categories, identified by wavelength (Du, Wa, Wb, Wc, Wd, We). Based on these measurement data, Du, Lw, Sw are calculated by the device and indicate the appearance level of the paint. Lower Du, Lw, Sw values represent better appearance performance. Good appearance performance is usually defined as satisfying both Lw < 5 and Sw < 20.
[0282] (8) Gloss and haze measurement
[0283] The gloss and haze of dried and cured coatings are evaluated by measuring the specular gloss of the surface using a gloss meter. Gloss is determined by projecting a beam of light onto the surface at a fixed intensity and angle and measuring the amount of reflected light at equal but opposite angles of 20° and 60°, respectively. Haze is caused by microscopic surface structures that slightly change the direction of reflected light to cause halos adjacent to the specular (gloss) angle. The surface has a small reflective contrast and a light opalescent effect. A gloss meter can quantify orange peel by measuring distinctness of image (DOI) as well as haze. Good appearance performance is usually defined as meeting both DOI>90 and haze<20.
[0284] (9) Acid corrosion resistance
[0285] Acid etch resistance is evaluated by 20° gloss retention after acid treatment. The acid treatment is performed by immersing the coating into a 0.35M Fe(II)SO4 solution in 0.5M H2SO4. During the test, the coating is completely covered with acid and stored at 70°C for 60 minutes. The 20° gloss before and after the acid treatment is compared. Higher gloss retention represents better performance in acid etch resistance. The 20° gloss retention of conventional 2K polyurethane or acid / epoxy clearcoats is approximately 70%.
[0286] (10) Alkali corrosion resistance
[0287] Alkali corrosion resistance is evaluated by the 20° gloss retention after alkaline treatment. Alkali treatment is performed by immersing the coating into a 1% sodium hydroxide solution. During the test, the coating is completely covered with the alkaline solution and stored at 70°C for 60 minutes. The 20° gloss before and after the acid treatment is compared. A higher gloss retention represents a better performance in alkaline corrosion resistance. The 20° gloss retention of conventional 2K polyurethane or acid / epoxy varnishes is approximately 60%.
Claims
1. A dual-reactive coating composition comprising a). 24 to 90% by weight of a crosslinkable silane-functional polymer; b). 9 to 75% by weight of unsaturated polyester; c). 0.5 to 10% by weight of an initiator; and d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition; wherein the unsaturated polyester is prepared by condensation of at least one monounsaturated linear aliphatic dicarboxylic acid or its anhydride and at least one saturated aliphatic diol; wherein the crosslinkable silane-functional polymer is prepared by polymerization of monomers comprising i) 20 to 50 wt% of a vinylalkoxysilane of formula I H2C=CH-(CH2) n -Si-(R1) m (R2) 3-m Formula I wherein R1 is an aryl or alkyl group having C1-C6, R2 is an alkoxy group having C1-C6, m is 0 or 1, and n is an integer from 0 to 3; ii) 50 to 80 wt% of (meth)acrylate monomers; and iii) 0 wt% to 30 wt% of a styrenic monomer, all weight percentages based on the total weight of the silane-functional polymer.
2. The dual reactive coating composition according to claim 1, wherein the crosslinkable silane functional polymer is prepared by polymerization of monomers comprising i) 20 to 50% by weight of vinyltrimethoxysilane; ii) 50 to 80 weight percent of at least one (meth)acrylate monomer selected from methyl methacrylate, n-butyl acrylate, ethylhexyl acrylate, and hydroxypropyl methacrylate; and iii) 0 to 30 weight percent of styrene, all weight percentages based on the total weight of the silane-functional polymer.
3. The dual reactive coating composition according to claim 1, wherein the crosslinkable silane functional polymer has a weight average molecular weight of less than 30,000.
4. The dual reactive coating composition according to claim 2, wherein the crosslinkable silane functional polymer has a weight average molecular weight of less than 30,000.
5. The dual reactive coating composition according to any one of claims 1 to 4, wherein the crosslinkable silane functional polymer has a hydroxyl value of 0 to 150 mg KOH / g and an acid value of 0 to 50 mg KOH / g.
6. The dual reactive coating composition according to any one of claims 1 to 4, wherein the unsaturated polyester has a weight average molecular weight of 200 to 20,000.
7. The dual reactive coating composition according to claim 5, wherein the unsaturated polyester has a weight average molecular weight of 200 to 20,000.
8. The dual reactive coating composition according to any one of claims 1 to 4, wherein the unsaturated polyester has a hydroxyl value of 0 to 350 mg KOH / g and an acid value of 0 to 150 mg KOH / g.
9. The dual reactive coating composition according to claim 5, wherein the unsaturated polyester has a hydroxyl value of 0 to 350 mg KOH / g and an acid value of 0 to 150 mg KOH / g.
10. The dual reactive coating composition according to claim 6, wherein the unsaturated polyester has a hydroxyl value of 0 to 350 mg KOH / g and an acid value of 0 to 150 mg KOH / g.
11. The dual reactive coating composition according to any one of claims 1 to 4, wherein the unsaturated polyester is prepared by condensation of at least one monounsaturated linear aliphatic dicarboxylic acid or anhydride thereof selected from maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, hexahydrophthalic acid, hexahydrophthalic anhydride and fumaric acid and at least one saturated aliphatic diol selected from neopentyl glycol, 1,4-butanediol, 1,6-hexanediol and cyclohexanedimethanol.
12. The dual reactive coating composition according to claim 5, wherein the unsaturated polyester is prepared by condensation of at least one monounsaturated linear aliphatic dicarboxylic acid or anhydride thereof selected from maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, hexahydrophthalic acid, hexahydrophthalic anhydride and fumaric acid and at least one saturated aliphatic diol selected from neopentyl glycol, 1,4-butanediol, 1,6-hexanediol and cyclohexanedimethanol.
13. The dual reactive coating composition according to claim 6, wherein the unsaturated polyester is prepared by condensation of at least one monounsaturated linear aliphatic dicarboxylic acid or anhydride thereof selected from maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, hexahydrophthalic acid, hexahydrophthalic anhydride and fumaric acid and at least one saturated aliphatic diol selected from neopentyl glycol, 1,4-butanediol, 1,6-hexanediol and cyclohexanedimethanol.
14. The dual reactive coating composition according to claim 8, wherein the unsaturated polyester is prepared by condensation of at least one monounsaturated linear aliphatic dicarboxylic acid or anhydride thereof selected from maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, hexahydrophthalic acid, hexahydrophthalic anhydride and fumaric acid and at least one saturated aliphatic diol selected from neopentyl glycol, 1,4-butanediol, 1,6-hexanediol and cyclohexanedimethanol.
15. The dual reactive coating composition according to any one of claims 1 to 4, wherein the initiator is at least selected from dibenzoyl peroxide (BPO), ethyl 2-oxocyclopentanecarboxylate (EOC) and benzopinacol (BP).
16. The dual reactive coating composition according to claim 5, wherein the initiator is at least selected from dibenzoyl peroxide (BPO), ethyl 2-oxocyclopentanecarboxylate (EOC) and benzopinacol (BP).
17. The dual reactive coating composition according to claim 6, wherein the initiator is at least selected from dibenzoyl peroxide (BPO), ethyl 2-oxocyclopentanecarboxylate (EOC) and benzopinacol (BP).
18. The dual reactive coating composition according to claim 8, wherein the initiator is at least selected from dibenzoyl peroxide (BPO), ethyl 2-oxocyclopentanecarboxylate (EOC) and benzopinacol (BP).
19. The dual reactive coating composition according to claim 11, wherein the initiator is at least selected from dibenzoyl peroxide (BPO), ethyl 2-oxocyclopentanecarboxylate (EOC) and benzopinacol (BP).
20. The dual reactive coating composition according to any one of claims 1 to 4, wherein the catalyst is selected from at least benzoic acid phosphate (PAP), amine-neutralized p-toluenesulfonic acid and amine-neutralized phosphate ester.
21. The dual reactive coating composition according to claim 5, wherein the catalyst is at least selected from the group consisting of benzoic acid phosphate (PAP), amine-neutralized p-toluenesulfonic acid and amine-neutralized phosphate ester.
22. The dual reactive coating composition according to claim 6, wherein the catalyst is at least selected from the group consisting of benzoic acid phosphate (PAP), amine-neutralized p-toluenesulfonic acid and amine-neutralized phosphate ester.
23. The dual reactive coating composition according to claim 8, wherein the catalyst is selected from at least benzoic acid phosphate (PAP), amine-neutralized p-toluenesulfonic acid and amine-neutralized phosphate ester.
24. The dual reactive coating composition according to claim 11, wherein the catalyst is selected from at least benzoic acid phosphate (PAP), amine-neutralized p-toluenesulfonic acid and amine-neutralized phosphate ester.
25. The dual reactive coating composition according to claim 15, wherein the catalyst is selected from at least benzoic acid phosphate (PAP), amine neutralized p-toluenesulfonic acid and amine neutralized phosphate ester.
26. The dual reactive coating composition according to claim 20, wherein the amine neutralized p-toluenesulfonic acid is NARCURE 2500 and / or the amine neutralized phosphate ester is NARCURE 4575.
27. The dual reactive coating composition according to any one of claims 1 to 4, wherein the crosslinkable silane functional polymer is prepared by a process comprising two steps: in a first step, a vinyl alkoxysilane monomer, a (meth)acrylate monomer and optionally a styrenic monomer and an initiator are mixed with an organic solvent and heated, and in a second step, the (meth)acrylate monomer and optionally a styrenic monomer and an initiator are added, wherein in the second step, the (meth)acrylate monomer and optionally a styrenic monomer are added in not less than two batches, and the time between each batch is not less than half an hour and the weight ratio between the (meth)acrylate monomer and the optional styrenic monomer added in each batch is 1:15 to 15:
1.
28. The dual reactive coating composition according to claim 5, wherein the crosslinkable silane functional polymer is prepared by a process comprising two steps: in a first step, a vinyl alkoxysilane monomer, a (meth)acrylate monomer and optionally a styrenic monomer and an initiator are mixed with an organic solvent and heated, and in a second step, the (meth)acrylate monomer and optionally a styrenic monomer and an initiator are added, wherein in the second step, the (meth)acrylate monomer and optionally a styrenic monomer are added in not less than two batches, and the time between each batch is not less than half an hour and the weight ratio between the (meth)acrylate monomer and the optional styrenic monomer added in each batch is 1:15 to 15:
1.
29. The dual reactive coating composition according to claim 6, wherein the crosslinkable silane functional polymer is prepared by a method comprising two steps: in a first step, a vinyl alkoxysilane monomer, a (meth)acrylate monomer and optionally a styrenic monomer and an initiator are mixed with an organic solvent and heated, and in a second step, the (meth)acrylate monomer and optionally a styrenic monomer and an initiator are added, wherein in the second step, the (meth)acrylate monomer and optionally a styrenic monomer are added in not less than two batches, and the time between each batch is not less than half an hour and the weight ratio between the (meth)acrylate monomer and the optional styrenic monomer added in each batch is 1:15 to 15:
1.
30. The dual reactive coating composition according to claim 8, wherein the crosslinkable silane functional polymer is prepared by a method comprising two steps: in a first step, a vinyl alkoxysilane monomer, a (meth)acrylate monomer and optionally a styrenic monomer and an initiator are mixed with an organic solvent and heated, and in a second step, the (meth)acrylate monomer and optionally a styrenic monomer and an initiator are added, wherein in the second step, the (meth)acrylate monomer and optionally a styrenic monomer are added in not less than two batches, and the time between each batch is not less than half an hour and the weight ratio between the (meth)acrylate monomer and the optional styrenic monomer added in each batch is 1:15 to 15:
1.
31. The dual reactive coating composition according to claim 11, wherein the crosslinkable silane functional polymer is prepared by a method comprising two steps: in a first step, a vinyl alkoxysilane monomer, a (meth)acrylate monomer and optionally a styrenic monomer and an initiator are mixed with an organic solvent and heated, and in a second step, the (meth)acrylate monomer and optionally a styrenic monomer and an initiator are added, wherein in the second step, the (meth)acrylate monomer and optionally a styrenic monomer are added in not less than two batches, and the time between each batch is not less than half an hour and the weight ratio between the (meth)acrylate monomer and the optional styrenic monomer added in each batch is 1:15 to 15:
1.
32. The dual reactive coating composition according to claim 15, wherein the crosslinkable silane functional polymer is prepared by a process comprising two steps: in a first step, a vinyl alkoxysilane monomer, a (meth)acrylate monomer and optionally a styrenic monomer and an initiator are mixed with an organic solvent and heated, and in a second step, the (meth)acrylate monomer and optionally a styrenic monomer and an initiator are added, wherein in the second step, the (meth)acrylate monomer and optionally a styrenic monomer are added in not less than two batches, and the time between each batch is not less than half an hour and the weight ratio between the (meth)acrylate monomer and the optional styrenic monomer added in each batch is 1:15 to 15:
1.
33. The dual reactive coating composition according to claim 20, wherein the crosslinkable silane functional polymer is prepared by a method comprising two steps: in a first step, a vinyl alkoxysilane monomer, a (meth)acrylate monomer and optionally a styrenic monomer and an initiator are mixed with an organic solvent and heated, and in a second step, the (meth)acrylate monomer and optionally a styrenic monomer and an initiator are added, wherein in the second step, the (meth)acrylate monomer and optionally a styrenic monomer are added in not less than two batches, and the time between each batch is not less than half an hour and the weight ratio between the (meth)acrylate monomer and the optional styrenic monomer added in each batch is 1:15 to 15:
1.
34. The dual reactive coating composition according to claim 26, wherein the crosslinkable silane functional polymer is prepared by a process comprising two steps: in a first step, a vinyl alkoxysilane monomer, a (meth)acrylate monomer and optionally a styrenic monomer and an initiator are mixed with an organic solvent and heated, and in a second step, the (meth)acrylate monomer and optionally a styrenic monomer and an initiator are added, wherein in the second step, the (meth)acrylate monomer and optionally a styrenic monomer are added in not less than two batches, and the time between each batch is not less than half an hour and the weight ratio between the (meth)acrylate monomer and the optional styrenic monomer added in each batch is 1:15 to 15:
1.
35. The dual reactive coating composition according to any one of claims 1 to 4, wherein it further comprises a silane functional sag control agent.
36. The dual reactive coating composition according to claim 6, wherein it further comprises a silane functional sag control agent.
37. The dual reactive coating composition according to claim 8, wherein it further comprises a silane functional sag control agent.
38. The dual reactive coating composition according to claim 11, wherein it further comprises a silane functional sag control agent.
39. The dual reactive coating composition according to claim 15, wherein it further comprises a silane functional sag control agent.
40. The dual reactive coating composition according to claim 20, wherein it further comprises a silane functional sag control agent.
41. The dual reactive coating composition according to claim 26, wherein it further comprises a silane functional sag control agent.
42. The dual reactive coating composition according to claim 27, wherein it further comprises a silane functional sag control agent.
43. A film obtained by curing and drying a dual reactive coating composition according to any one of claims 1 to 42.
44. A substrate coated with a dual reactive coating composition according to any one of claims 1 to 42.
45. A substrate according to claim 44, wherein the substrate is an automobile.
46. A substrate according to claim 44, wherein the substrate is a truck.
47. A method for preparing a dual reactive coating composition according to claim 1 by mixing the following components a). 24 to 90% by weight of a crosslinkable silane-functional polymer; b). 9 to 75% by weight of unsaturated polyester; c). 0.5 to 10% by weight of an initiator; and d). 0.5 wt % to 10 wt % of a catalyst, all weight percentages based on the total weight of the coating composition; wherein the unsaturated polyester is prepared by condensation of at least one monounsaturated linear aliphatic dicarboxylic acid or its anhydride and at least one saturated aliphatic diol; The crosslinkable silane functional polymer is prepared by polymerization of monomers comprising i) 20 to 50 wt% of a vinylalkoxysilane of formula I H2C=CH-(CH2) n -Si-(R1) m (R2) 3-m Formula I wherein R1 is an aryl or alkyl group having C1-C6, R2 is an alkoxy group having C1-C6, m is 0 or 1, and n is an integer from 0 to 3; ii) 50 to 80 wt% of (meth)acrylate monomers; and iii) 0 wt% to 30 wt% of a styrenic monomer, all weight percentages based on the total weight of the silane-functional polymer.
48. A roll-to-roll coating composition comprising the dual reactive coating composition according to any one of claims 1 to 42, a reactive diluent and an additive, wherein the solid content of the obtained roll-to-roll coating composition is not less than 90 wt%.
49. The roll-to-roll coating composition according to claim 48, wherein the solid content of the resulting roll-to-roll coating composition is not less than 95% by weight.
50. A 1K varnish composition comprising the dual reactive coating composition according to any one of claims 1 to 42, a reactive diluent, an additive and a cosolvent, wherein the VOC (volatile organic compound) of the obtained varnish composition is not more than 420 g / L.
51. The 1K varnish composition according to claim 50, wherein the VOC (volatile organic compound) of the resulting varnish composition is not more than 350 g / L.
Citation Information
Patent Citations
Free radical-cation hybrid photocuring POSS-contained coating and preparation method thereof
CN109111829A
UV curable coating composition
CN1906253A
Process for multi-layer coating of substrates
WO2003106578A1